COVID-19 Vaccine Hesitancy in Denmark and Russia: A qualitative typology at the nexus of agency and health capital - Anna Schneider-Kamp (SSM: Qualitative Research in Health, 2022)
Vaccination of the world population is being embraced by 184 countries as the main strategy to end the COVID-19 pandemic; vaccination rates are stalling even in countries with high vaccine availability, though. This article investigates the phenomenon of vaccine hesitancy in two such countries, the Kingdom of Denmark and the Russian Federation, through a qualitative study of the different types of hesitancy to COVID-19 vaccination programs and their underlying mechanisms. The analysis reveals a typology along the dimensions of agency and health capital: resisting hesitancy based on mistrust of authority, paralyzed hesitancy based on personal fear, informed hesitancy based on informed choice, and empowered hesitancy based on empowered choice. While the mechanisms underlying vaccine hesitancy are to a great extent comparable between the two countries, differences in population size, societal cohesion, and political culture seem to impact the prevalence and severity of types and, thereby, the outcomes of national COVID-19 vaccination programs and national campaigns for mitigating COVID-19 vaccine hesitancy. The implications of these findings extend beyond the particular context of COVID-19 and the countries studied, supporting and nuancing existing models for vaccine hesitancy, as well as providing a starting point for tailored campaigns for mitigating vaccine hesitancy.